Floating aortic thrombus with celiac artery embolus presenting with chronic epigastric and right upper quadrant pain: A case report. Issue 3 (12th January 2021) - Jahanshahi, Fatemeh; Kalantar Motamedi, Alireza
Abstract: Arterial occlusion may be the cause of chronic pain, and vascular diagnostic procedures should be a part of the workup in patients with unexplained chronic visceral pain. Abstract : Arterial occlusion may be the cause of chronic pain, and vascular diagnostic procedures should be a part of the workup in patients with unexplained chronic visceral pain.